Design and structure of the Estonian HIV Cohort Study (E-HIV). Issue 11 (November 2015) - Soodla, Pilleriin; Rajasaar, Heli; Avi, Radko; Zilmer, Kai; Kink, Kersti; Novikova, Liilia; Huik, Kristi; Maimets, Matti; Lutsar, Irja
Abstract: Background: Estonia is experiencing the new Eastern Europe human immunodeficiency virus (HIV) epidemic, with the highest incidence of new infections in the EU. We describe demographic changes, HIV-related laboratory parameters and co-infections during the concentrated HIV epidemic using the Estonian HIV Cohort Study (E-HIV) database, founded in 2009. Methods: All 3750 subjects in the E-HIV database on December 31, 2013 were included. Subjects were divided into risk groups: people who inject drugs (PWIDs), sexual transmission (heterosexual/homosexual), and other (perinatal) or unknown risk group. Subjects diagnosed before 2009 (first period) and after (second period) were analyzed separately. Results: The mean age at diagnosis has increased from 22.8 years (interquartile range (IQR) = 19.5–27.2) to 29.7 years (IQR = 25.3–36.2) ( p < 0.001) between the first and second periods. PWIDs were younger than other transmission groups (23.2 vs 27.1; p < 0.001). There is a statistical difference in the route of transmission among genders, with overall increasing sexual transmission. The most common AIDS-defining illness was tuberculosis (0.5%). HIV/hepatitis C (HCV) co-infection was diagnosed in 42% of cases. The population median CD4 + cell count at diagnosis has declined over the years; in total 53% have been late presenters. Half of the patients are receiving antiretroviral treatment (cART). The most common combinations are nucleoside reverse transcriptase inhibitor (NRTI) backbone plus protease inhibitors (PIs) (57%) or NRTI backbone + non-NRTIs (42%). Conclusion: The E-HIV enables us to fill the gap in the lack of data on the course of the new Eastern European HIV epidemic. These data demonstrate that the HIV epidemic in Estonia is moving from PWIDs to the general population, suggesting that prevention measures and testing guidelines should be revised.